1980
DOI: 10.1038/bjc.1980.34
|View full text |Cite
|
Sign up to set email alerts
|

Association of gross virus-associated cell-surface antigen with liposomes

Abstract: Summary.-Gross Cell-Surface Antigen (GCSAa) was obtained from W/Fu (C58NT)D lymphoma cells by Nonidet P40(NP40) or 3M KC1 extraction and further purified by Sephadex G200 filtration. GCSAa was associated with lipids (dipalmitoylphosphatidycholine, cholesterol and dicetylphosphate, in molar ratios of 7:2:1) to form multilamellar liposomes. The amount of protein associated with liposomes was found to be proportional to the protein concentration of the sensitizing cellular extract and to the amount of phospholipi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1980
1980
1987
1987

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…This could be attributed neither to a difference in antigen dose, since the in vitro specific GCSAa activities of both types of cellular extract used in these experiments were comparable, nor to a difference in GCSAa association with liposomes, since it has been shown in a previous work that the liposome composition and the distribution of GCSAa among liposomal structure are almost identical whatever the sensitizing cellular extract used (Sakai et al, 1980). Nevertheless, it may be questioned whether the 2 different antigen-solubilization procedures lead to GCSAa-bearing molecules of identical immunogenicity, since 3M KCI extraction may induce proteolytic cleavage (Mann, 1972) and since detergent solubilization produces micellar association of the solubilized molecules (Helenius & Simons, 1975).…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…This could be attributed neither to a difference in antigen dose, since the in vitro specific GCSAa activities of both types of cellular extract used in these experiments were comparable, nor to a difference in GCSAa association with liposomes, since it has been shown in a previous work that the liposome composition and the distribution of GCSAa among liposomal structure are almost identical whatever the sensitizing cellular extract used (Sakai et al, 1980). Nevertheless, it may be questioned whether the 2 different antigen-solubilization procedures lead to GCSAa-bearing molecules of identical immunogenicity, since 3M KCI extraction may induce proteolytic cleavage (Mann, 1972) and since detergent solubilization produces micellar association of the solubilized molecules (Helenius & Simons, 1975).…”
Section: Discussionmentioning
confidence: 71%
“…It cannot be excluded that the adjuvant effect exerted by liposome association of the antigen may be due to a membrane presentation effect since it has been shown that solubilized membrane antigen can stimulate lymphocytes in vitro when exposed on liposomes (Curman et al, 1978;Engelhard et al, 1978). However it is worth noting that the sensitized liposome used here exposed only a small proportion of the associated GCSAa at their surface (Sakai et al, 1980).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…For instance, glycosylation has been shown to influence the recognition by the immune system of influenza virus hemagglutinin and murine leukemia virus gp7O glycoproteins (40). The presentation of a protein also can greatly influence its immunogenicity (41)(42)(43). While neither processing nor presentation may be necessary for the production of neutralizing antibodies in every case, the epitopes needed for protective immune responses against a particular pathogen may be in question.…”
Section: Resultsmentioning
confidence: 99%
“…According to the technique described by Sakai et al [12], nega tively charged multilamellar liposomes were prepared by dispers ing a film of dipalmitoyphosphatidyl choline, cholesterol and diacetylphosphate in 7:2:1 molar ratio in a solution of DNP-HGG or of DNP-BSA. The liposome suspension was kept 30 min at room temperature, then diluted with cold saline and centrifuged at 30,000 g for 30 min.…”
Section: Preparation Of Liposomesmentioning
confidence: 99%